Предмет: Математика,
автор: анна1555
упростите выражение !!
Приложения:
Ответы
Автор ответа:
0
[(sinα+cosα)²-1]/(tgα-sinα·cosα) -2/(sin²(π+α))=
=(sin²α+2sinα·cosα+cos²α-1)/(sinα/cosα-sinα·cosα) -2/(sin²α)=
=(2sinα·cosα)/[sinα(1-cos²α)/cosα] -2/(sin²α)=2[cos²α/sin²α]-2/(sin²α)=
=2[(cos²α-1)/sin²α]=2sin²α/sin²α=2
=(sin²α+2sinα·cosα+cos²α-1)/(sinα/cosα-sinα·cosα) -2/(sin²α)=
=(2sinα·cosα)/[sinα(1-cos²α)/cosα] -2/(sin²α)=2[cos²α/sin²α]-2/(sin²α)=
=2[(cos²α-1)/sin²α]=2sin²α/sin²α=2
Похожие вопросы
Предмет: Математика,
автор: aripovafiruza9
Предмет: Психология,
автор: AlexanderWFTS
Предмет: Математика,
автор: aisanabakytzhan09
Предмет: Математика,
автор: yaver69